Teacher's Role in Implementing Learning with a Joyful Differentiated Approach in the Classroom - Wardani, Devina Kusuma; Marmoah, Sri; Sudiyanto, Sudiyanto (Universitas Sebelas Maret, 2025)
A differentiated approach is a learning strategy that adapts content, process, product, and environment to learners’ readiness, interests, and styles with the teacher as the key facilitator. The purpose of this study is to analyze the role of teachers in joyful differentiated learning through proven effective strategies by conducting a systematic review. This research uses the Systematic Literature Review (SLR) method, totaling 10 Scopus reputable articles with relevant topics published in 2021-2025. This research shows that teachers have an important role in the success of fun differentiated learning, where learning adapts to the characteristics of students and creates learning diversity based on content, process, product, and a pleasant learning environment such as using interactive media and varied learning models by adjusting students' learning styles. So that learning in the classroom runs actively and fun. This research contributes significantly to deepening the understanding of the role of teachers in fun differentiated learning, as well as enriching the literature in learning development.